Research on Academic Information System Unnes Using Technology Acceptance Model (TAM) - Hardyanto, Wahyu; Sugiyanto, Sugiyanto; Purwinarko, Aji; Adhi, Aryono (KnE Social Sciences, 2019)
Online assessment has been carried out research on academic information system Unnes using Technology Acceptance Model (TAM) whose goal is to achieve accountability in academic application by taking the Graduate Program Unnes sampling. The method used to carry out this research through interviews/in dept interviews, documentation and questionnaires. Analyses were performed using analysis of Structural Equation Modeling (SEM) based covariance AMOS (Analysis of Moment Structures). The results obtained overall, Knowledge of Search Domain has no effect on Perceived Ease of Use. However, CMIN / DF qualiﬁed, because it has a value of≤2. Keywords: Academic Information System, TAM, SEM